Evaluation of effect of amitriptyline and pregabalin on heart rate variability in neuropathic pain in non-diabetic patients - Srivastava, Rohan; Kantharia, N. D. (International Journal of Research in Medical Sciences, 2022)
Background: The effects of amitriptyline and pregabalin on heart rate variability (HRV) in patients with neuropathic pain in non-diabetic patients are poorly understood in India. The present study was conducted to evaluate the effect of amitriptyline and pregabalin on heart rate variability (HRV) and neuropathic pain in non-diabetic patients. Methods: Forty adult patients (aged 18-65 years) of either sex diagnosed with neuropathic pain were divided into two groups. The study was prospective open label and observational study. Amitriptyline 10 mg once a day was given to group 1 while group 2 received pregabalin 75 mg once a day and HRV and pain score were recorded; and post-treatment data at 2 and 4 weeks were compared with pre-treatment values (control). All the statistical analysis was performed by using Statistical package for social sciences (SPSS) 20.0 software. Results: Both amitriptyline and pregabalin have increased HRV and reduced neuropathic pain intensity after 2- and 4-weeks treatment. The correlation between HRV and neuropathic pain was not observed. Conclusions: To conclude both the drugs have significantly increased HRV and reduced the pain intensity; but no correlation was observed between increased HRV and reduced pain intensity.